If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1.5(4x-10)=7
We simplify the equation to the form, which is simple to understand
1.5(4x-10)=7
Reorder the terms in parentheses
+(+6x-15)=7
Remove unnecessary parentheses
+6x-15=+7
We move all terms containing x to the left and all other terms to the right.
+6x=+7+15
We simplify left and right side of the equation.
+6x=+22
We divide both sides of the equation by 6 to get x.
x=3.6666666666667
| 0=5t^2+16t+16 | | 6n+n+14=o | | -309=12v+3 | | 3(6x+7)=16-2x | | 10(x+5)+x-10=84 | | 2-7(4a+1)=-89 | | 13t-15t=12 | | 2x+2=20-4x | | 6x-14=15+5x | | -5n-11=29 | | 17.5+(-42.2)= | | (3x-17)(9x^2-42x+49)=0 | | 5x-23=10x-47 | | 1+4n=-13+5n-8n | | 8x=12+x^2 | | 5x+(x-2)+3(x-4)=1 | | 17.5-(42.2)= | | -m^2+14-16m^2+13+m^2= | | (4x-5)(6x+5)= | | 108=-5x+3 | | x-2(x+3)+4(x-1)=2 | | x-2(x+3)+4(x-1)=22 | | -5(3x-5)=-15x+25 | | 2x(x+3y+4z)= | | 11*1.86-12= | | X^2+1x+.25=0 | | -31-9x=-6x+32 | | y-x^2+6x=k | | 5x-10+(-9)=-7+7x | | 8x+11=3x-19 | | -14b-5=12b+8 | | -20-6x=6-4x |